Combined Expression of Plasma Thrombospondin‐2 and CA19‐9 for Diagnosis of Pancreatic Cancer and Distal Cholangiocarcinoma: A Proteome Approach. (14th January 2020) - Le Large, Tessa Y.S.; Meijer, Laura L.; Paleckyte, Rosita; Boyd, Lenka N.C.; Kok, Bart; Wurdinger, Thomas; Schelfhorst, Tim; Piersma, Sander R.; Pham, Thang V.; van Grieken, Nicole C.T.; Zonderhuis, Barbara M.; Daams, Freek; et al.
Abstract: Background: Minimally invasive diagnostic biomarkers for patients with pancreatic ductal adenocarcinoma (PDAC) and distal cholangiocarcinoma (dCCA) are warranted to facilitate accurate diagnosis. This study identified diagnostic plasma proteins based on proteomics of tumor secretome. Materials and Methods: Secretome of tumor and normal tissue was collected after resection of PDAC and dCCA. Differentially expressed proteins were measured by mass spectrometry. Selected candidate biomarkers and carbohydrate antigen 19‐9 (CA19‐9) were validated by enzyme‐linked immunosorbent assay in plasma from patients with PDAC ( n = 82), dCCA ( n = 29), benign disease (BD; n = 30), and healthy donors (HDs; n = 50). Areas under the curve (AUCs) of receiver operator characteristic curves were calculated to determine the discriminative power. Results: In tumor secretome, 696 discriminatory proteins were identified, including 21 candidate biomarkers. Thrombospondin‐2 (THBS2) emerged as promising biomarker. Abundance of THBS2 in plasma from patients with cancer was significantly higher compared to HDs ( p < .001, AUC = 0.844). Combined expression of THBS2 and CA19‐9 yielded the optimal discriminatory capacity (AUC = 0.952), similarly for early‐ and late‐stage disease (AUC = 0.971 and AUC = 0.911). Remarkably, this combination demonstrated a power similar to CA19‐9 to discriminate cancer from BD (AUC = 0.764), and THBS2 provided an additive value in patients with high expression levels of bilirubin. Conclusion: Our proteome approach identified a promising set of candidate biomarkers. The combined plasma expression of THBS2/CA19‐9 is able to accurately distinguish patients with PDAC or dCCA from HD and BD. Implications for Practice: The combined plasma expression of thrombospondin‐2 and carbohydrate antigen 19‐9 is able to accurately diagnose patients with pancreatic cancer and distal cholangiocarcinoma. This will facilitate minimally invasive diagnosis for these patients by distinguishing them from healthy individuals and benign diseases. Abstract : This article identifies diagnostic plasma proteins to distinguish patients with pancreatic ductal adenocarcinoma and distal cholangiocarcinoma from benign disease and health donors and evaluates these new markers for additive value with CA19‐9 at different disease stages.